Clinical Effectiveness of Cardiac Noninvasive Diagnostic Testing in Outpatients Evaluated for Stable Coronary Artery Disease - Idan Roifman; Atul Sivaswamy; Anna Chu; Peter C. Austin; Dennis T. Ko; Pamela S. Douglas; Harindra C. Wijeysundera (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Despite more than 4 million cardiac noninvasive diagnostic tests (NIT) being performed annually for stable coronary artery disease in the United States, it is unclear whether they are associated with downstream improvements in outcomes when compared with no testing. We sought to determine whether NIT was associated with reduced downstream major adverse cardiovascular events when compared with not testing. Methods and Results We conducted a population‐based study of ≈1.5 million patients undergoing chest pain evaluation in Ontario, Canada. Patients were categorized into NIT and no‐testing groups. Cause‐specific proportional hazards models were used to compare the rate of major adverse cardiovascular events (composite outcome of unstable angina, acute myocardial infarction or cardiovascular mortality and each constituent) between the 2 groups after adjusting for clinically relevant covariates. The rate of the composite outcome was ≈25% lower for patients undergoing noninvasive testing (hazard ratio [HR], 0.77; 95% CI, 0.75–0.79). The benefits of testing were consistent for all 3 constituents of the composite; unstable angina (HR, 0.87; 95% CI, 0.82–0.93 for the NIT versus the no‐testing group), myocardial infarction (HR, 0.83; 95% CI, 0.79–0.86 for the NIT versus the no‐testing group) and cardiovascular mortality (HR, 0.68; 95% CI, 0.65–0.72 for the NIT versus the no‐testing group). Conclusions Our large population‐based study reports an ≈25% reduction in major adverse cardiovascular events that was independently associated with NIT in outpatients being evaluated for stable angina. This study demonstrates the prognostic importance of NIT versus no testing on the health of contemporary populations.